Pengaruh penggunaan modul dalam pembelajaran kimia berbasis proyek terhadap hasil belajar siswa kelas XI semester 1 pada materi termokimia - Shella Julia Rani Hulu; Murniaty Simorangkir (ARKA INSTITUTE, 2022)
This study aims to evaluate the impact of using modules in project-based chemistry learning on learning outcomes, learning effectiveness, and student responses to class XI thermochemistry material in semester 1. The study population involved students in class XI IPA SMA Negeri 14 Medan in the 2021/2022 academic year. The sample was selected using purposive sampling technique, with class XI MIPA 4 as the experimental class using project-based modules, and class XI MIPA 2 as the control class with conventional learning. The research instrument is a chemistry learning outcomes test on thermochemistry material with 25 multiple choice questions that have been validated and have high reliability. Data on student learning outcomes were tested using a one-sided t test. The results showed that the use of modules in project-based chemistry learning significantly improved student learning outcomes, showing better learning effectiveness compared to conventional learning. In addition, students' responses to learning with project-based modules on thermochemical materials were also positive. Thus, it is concluded that the project-based module has a positive and significant influence on student learning outcomes in thermochemistry.